Faktor – Faktor Yang Mempengaruhi Profitabilitas Pada Perusahaan Perbankan - Richard Eduardo, Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to obtain an evidence on the effect of capital adequacy ratio, non-performing loan, net interest margin, operational efficiency, Indonesia GDP growth rate, Bank Indonesia interest rate on return on asset and return on equity as bank profitability representative in banking companies listed in Indonesian Stock Exchange during 2017-2019. This study uses purposive sampling as the sampling technique and uses 28 banking companies as research sample. The results of this study show that net interest margin have positive influence towards return on asset and return on equity, capital adequacy ratio have positive influence towards return on equity, while operational efficiency has negative influence towards return on asset and return on equity.